2014
DOI: 10.1016/j.econlet.2014.03.008
|View full text |Cite
|
Sign up to set email alerts
|

On conditions in central limit theorems for martingale difference arrays

Abstract: An alternative central limit theorem for martingale difference arrays is presented. It can be deduced from the literature but it is not stated as such. It can be very useful for statisticians and econometricians. An illustration is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2026
2026

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Proof. It is shown in Alj et al (2014) and Gaenssler et al (1978) that the conditional Lindeberg condition follows from the unconditional Lyapunov condition. We will show in the following, that n j=2 E|Y n,j | 4 = o(1) and decompose n j=2 E|Y n,j | 4 = L n,1 + L n,2 + L n,3 + L n,4 , where…”
Section: B Auxiliary Resultsmentioning
confidence: 99%
“…Proof. It is shown in Alj et al (2014) and Gaenssler et al (1978) that the conditional Lindeberg condition follows from the unconditional Lyapunov condition. We will show in the following, that n j=2 E|Y n,j | 4 = o(1) and decompose n j=2 E|Y n,j | 4 = L n,1 + L n,2 + L n,3 + L n,4 , where…”
Section: B Auxiliary Resultsmentioning
confidence: 99%
“…The proof continues as in Theorem 2 and 2' of [1], using a weak law of large numbers for a mixingale array in [53] and referring to Theorems 1 and 1' of [1], which make use of a central limit theorem for a martingale difference array (see [54]), modified with a Lyapunov condition (see [55]).…”
Section: Discussionmentioning
confidence: 99%
“…Proof. It is similar to Alj et al (2014) (except that there k n = n and σ = 1 were assumed) where it is shown that it is a consequence of Brown (1971), more precisely Brown and Eagleson (1971), and of Gaenssler et al (1978).…”
Section: Proofsmentioning
confidence: 91%
“…As shown by Gaenssler et al (1978), the unconditional Lindeberg condition implies the conditional Lindeberg condition. Since Lyapunov conditions are stronger than Lindeberg conditions, Alj et al (2014) have fully justified the replacement mentioned above. t ; t = 1, ..., k n , n ∈ N} be a scalar zeromean square-integrable martingale difference array, and {k n } an increasing integer sequence with {k n } ↑ ∞.…”
Section: Proofsmentioning
confidence: 97%
See 1 more Smart Citation